Mixed topological semimetals driven by orbital complexity in two-dimensional ferromagnets - Chengwang Niu (Nature Portfolio, 2019)
Whether topological semimetal states can emerge in two-dimensional magnetic materials remains less understood. Here, Niu and Hanke et al. propose the concepts of mixed Weyl and nodal-line semimetallic phases by including the magnetization direction into the topological analysis in two-dimensional ferromagnets.